2005
DOI: 10.1097/01.imi.0000190492.41439.8c
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Evaluation of the St. Jude Medical Aortic Connector for Aortic-to-Autologous Vessel Graft Anastomoses

Abstract: Background Evolving technologies of proximal anastomosis devices meet the endeavor of surgeons to minimize manipulation of the ascending aorta during surgical myocardial revascularization. The objective of this study was to compare the patency rate of the saphenous vein coronary bypass grafts in which the proximal anastomoses were performed with automatic connector devices to the suture technique. Methods Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…8 Diegeler and associates reported a prospective evaluation of St. Jude Medical's second-generation aortic connector (Symmetry G2) and found early and midterm patency rates comparable to conventional sutured anastomoses at 6 month follow-up angiography. 9 At the March 18 th 2004 meeting of the FDA's Circulatory System Devices Panel, a total of 213 adverse event reports related to the Symmetry aortic anastomotic device were retrieved from the FDA's Medical Device Reporting System (MDR) database. There were 23 reports of death, 185 reports of injury, and 5 reports of malfunction.…”
Section: Discussionmentioning
confidence: 99%
“…8 Diegeler and associates reported a prospective evaluation of St. Jude Medical's second-generation aortic connector (Symmetry G2) and found early and midterm patency rates comparable to conventional sutured anastomoses at 6 month follow-up angiography. 9 At the March 18 th 2004 meeting of the FDA's Circulatory System Devices Panel, a total of 213 adverse event reports related to the Symmetry aortic anastomotic device were retrieved from the FDA's Medical Device Reporting System (MDR) database. There were 23 reports of death, 185 reports of injury, and 5 reports of malfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Although clinical practice inclined to reject the use of these devices, other studies reported a positive experience with advanced devices; Diegeler et al compared the patency rate of the saphenous vein coronary bypass grafts in which the proximal anastomoses were performed with second-generation automatic connector devices to the suture technique 7. This was examined in 86 patients who underwent CABG with at least one vein graft anastomosed to the ascending aorta with the Symmetry G2 connector.…”
Section: Proximal Anastomosis Devicementioning
confidence: 99%